Net Foreign Assets and Imperfect Financial Integration: An Empirical Approach - Selaive, Jorge (2008)
Researchers have documented extensive empirical evidence on both risk sharing across countries and the uncovered interest rate parity (UIP) condition. This paper involves investigating the empirical implications of imperfectly integrated financial markets resulting from the two phenomena. Under this asset market structure, the net foreign assets (NFA) position of a country affects both the risk-sharing condition and the UIP. Strong evidence exists for Organization for Economic Cooperation and Development (OECD) countries that the NFA contribute to the lack of risk sharing across countries. Similarly, in terms of the UIP, the NFA can capture a time-varying risk premium for a small group of countries over short-term horizons.